2016
DOI: 10.1007/s00535-016-1188-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a serum transglutaminase threshold value for the noninvasive diagnosis of symptomatic adult celiac disease patients: a retrospective study

Abstract: The anti-tTG serum levels/cut-off ratio correlates with the degree of duodenal lesions and, if used with the threshold value >3.6, could avoid endoscopy with biopsy in about 75 % of seropositive adults waiting for CD diagnosis. However, since this procedure could also imply CD diagnosis in almost 3 % of seropositive patients with normal villous architecture, a consensus opinion is needed to suggest its use in the diagnosis of adult CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…For this reason, while creating an ESPGHAN‐like algorithm for adult patients, it should be taken into consideration that, the clinical, serological, and tissue damage levels are different from pediatric patients, so the cutoff values of the serological tests also differ. Our results were consistent with the study of Tola et al that different threshold levels for pediatric and adult patients must be detected for IgA tTG levels.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…For this reason, while creating an ESPGHAN‐like algorithm for adult patients, it should be taken into consideration that, the clinical, serological, and tissue damage levels are different from pediatric patients, so the cutoff values of the serological tests also differ. Our results were consistent with the study of Tola et al that different threshold levels for pediatric and adult patients must be detected for IgA tTG levels.…”
Section: Discussionsupporting
confidence: 94%
“…When ESPGHAN's threshold value for children was taken into consideration (>200 IU/mL), it was found that the sensitivity decreased to 81%. Similarly, in a study of adult patients in which the threshold value was determined by ROC curve analysis, with the determined anti‐tTG IgA threshold (>3.6‐fold higher), the highest sensitivity (76.8%) was achieved but the sensitivity decreased to 33.5% when the threshold value recommended for children was used …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When CD is suspected, the first diagnostic step is most often the analysis of anti-tissue transglutaminase (tTGIgA) [14]. However, this test is also used during follow-up to verify the adherence to a gluten-free diet because it has been shown that more than 90 percent of CD patients on a gluten-free diet will have negative serologies by 5 years [15].…”
Section: Introductionmentioning
confidence: 99%
“…They referred to our Gastroenterology Unit from January 2017 to December 2019. Their CD diagnosis had been previously made according gluten-related signs and symptoms, serum EMA and anti-tTG antibodies positive results, and the histological finding of duodenal villous atrophy (Marsh-Oberhuber type IIIA, B, or C) [20][21][22].…”
Section: Patientsmentioning
confidence: 99%